Kualitas Pengaruh Konten Instagram dan Sosial Media Marketing terhadap Minat Beli Konsumen pada Rio Home Studio - Saleh, Sonni Rahmat; Suherman, Jajang (Jurnal Dimamu, 2024)
In today's digital era, the quality of Instagram content and social media marketing in increasing consumer buying interest is the most important thing for a company, decreasing consumer buying interest. This study aims to determine the influence of the quality of Instagram content and social media marketing on consumer buying interest in Rio Home Studio. This study uses a quantitative approach, the sample used is propability sampling and the respondent criteria, namely Instagram accounts that follow @riohomestudio accounts, using 93 samples distributed through Instagram directorate messages. The testing techniques in this study use validity and reliability tests, classical assumption tests consisting of normality tests, multicoloniality tests, and heteroscenity tests, as well as multiple linear regression analysis consisting of hypothesis tests, namely t tests and f tests, and determination coefficient analysis, processed using SPSS 23. The results of this study show that: X1 has a positive effect on Y, as evidenced by the calculated t value of 5.794, the regression coefficient has a positive value of 0.000. X2 has a positive effect on Y, as evidenced by the calculated t value of 5.794, the regression coefficient has a positive value of 0.000. X1 and X2 have a positive effect on Y. It is evidenced by the result of f calculation of 2.36 with a significance of 0.000. The magnitude of the influence of X1 and X2 on Y is evidenced by the adjusted R square value of 81.5% and the remaining 18.5% is influenced by other variables outside this research model. From this study, it can be concluded that the quality of Instagram content and social media marketing has a positive effect on consumer buying interest.